Integration of design structure matrix and modular function deployment for mass customization and product modularization: a case study on heavy vehicles - Forti, Antonio Wagner [UNESP]; Ramos, César Coutinho; Muniz, Jorge [UNESP] (Springer Nature, 2023)
This work presents the integrating process of two modularization methods: design structure matrix (DSM) and modular function deployment (MFD), to products with many components commonly found in the automotive industry. To validate this process, the authors and a cross-functional team worked on the modularization process of an air rear suspension system for heavy vehicles with 44 components. The DSM method was used first as a screening method. Its application generated the first modules reducing the number of components, since the fewer components the product has, the less laborious the application of the MFD method, and the more suitable the results (final set of modules). Therefore, the modularization process started with the DSM method base on a binary square matrix that shows the presence or absence of relationships between pairs of components in a system. A DSM algorithm reordered the binary square matrix elements to generate the preliminary modules. That way, 26 of the 44 components were grouped into eight modules that became new components, reducing the initial number of components from 44 to 26 (44 − 26 + 8). The MFD method incorporated the customer requirements using the quality function deployment (QFD), the engineering point of view utilizing the design property matrix (DPM), and the strategies of the company employing the module indication matrix (MIM) in the modularization process. The QFD matrix, DPM, and MIM union formed the product management matrix (PMM). A dendrogram helped the cross-functional team visualize the hierarchical relationship between the DPM and MIM components and analyze the modules’ set. The cross-functional team chose seven final suitable modules considering components mounting in the assembly line and the supply chain of components too. This systematic modularization process showed up efficiently and made the work of the cross-functional team easy. Finally, the cross-functional team recommended the company board invest in knowledge management tools to assist the future cross-functional teams in replicating this modularization process in other heavy vehicle systems.
Keywords: Design techniques; Hierarchical clustering; Module design; Product development; Quality function deployment